The Influence Of Complementary Murottal Al-Qur'an Therapy On The Anxiety Of Pregnant Women In The 3rd Trimester In The Working Area Of The Payung Sekaki Health Center - Dewi Sartika Siagian; Nurazlinda Nurazlinda; Rini Hariani Ratih (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Background anxiety in pregnant women has become the highest problem over the last 5 years. Indonesia is one of the countries with a high level of anxiety in the third trimester of pregnancy, namely 69.89%, as a result of which it increases the risk of LBW, prematurity and prolonged labor. Management of anxiety in the third trimester of pregnancy before delivery can be done with complementary therapy Murottal Al-Quran . The aim is to determine the effect of complementary murottal Al Qur'an therapy on anxiety levels in third trimester pregnant women in the working area of the Payung Sekaki Community Health Center, Pekanbaru City, Riau. Method This research design uses a quasi-experimental method with a one group pretest-posttest design. This research was conducted in June 2024 for 3 weeks in the working area of the Payung Sekaki Community Health Center, Pekanbaru City. The sample in this study was third trimester pregnant women with a sampling technique using purpose sampling. The instruments in this research consisted of VAS sheets, cellphone audio murottal Al Qur'an. The data analysis technique uses univariate and bivariate analysis using the Dependent T test and Paired Samples Tset test in SPSS. The results of this study showed that the difference in the influence of anxiety before was 6.3% and anxiety after the intervention was 3.46%. The statistical test results were found to be significant where p < 0.05 with a p value of 0.010. The conclusion is that complementary murottal Al-Qur'an therapy on anxiety levels in third trimester pregnant women can reduce anxiety at the time of delivery in third trimester pregnant women in the working area of the Payung Sekaki Community Health Center, Pekanbaru City. Keywords: Anxiety, Murottal Al-Quran, Third trimester mothers